Cyber Notary di Era Globalisasi 4.0: Suatu Kebutuhan Ataukah Ancaman - R, Ngurah Justia Dharmadyawan; Dharmawan, Ni Ketut Supasti (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
This study aims to acknowledge and to analyze the capacity and the juridical power of the concept of cyber notary, in terms of Notary Public to carry out their duties, functions and authorities as Public Officials in the era of globalization 4.0. Furthermore, aims to perceive the opportunities that cyber notary can be applied into Indonesian’s legal system. This study uses normative legal research with the statue approach and conceptual approach, with primary and secondary legal materials. The result of this study indicates that UUJN-P (The Law on The Position of Notary Public) has presented the concept of cyber noatary, but it’s implementation still needs the necessary update of the laws and regulations, specifically that relates to the process of making the electronic-based deeds. For Notary to apply the concept of cyber notary in carrying out their duties, functions, and authorities not limited to participate the development of technology in this era of globalization.